EFFECTS OF ACETYLSALICYLIC ACID AND CLOPIDOGREL ON MORPHOFUNCTIONAL STATUS OF ERYTHROCYTES IN PATIENTS WITH ACUTE CORONARY SYNDROME - A. L. Alyavi; R. A. Rakhimov; B. A. Alyavi (Столичная издательская компания, 2016)
Aim. In patients with acute coronary syndrome (ACS) to study an aggregation activity and morphology of erythrocytes and to assess their changes during therapy with acetylsalicylic acid, clopidogrel and combined antiplatelet therapy (acetylsalicylic acid and clopidogrel). Material and methods. 98 patients (67 men and 31 women, aged 59,6±10,8 y.o.) with ACS were included in the study. Patients were split in 3 groups depending on prescribed antiplatelets (acetylsalicylic acid; clopidogrel; acetylsalicylic acid+clopidogrel). Aggregation activity and morphofunctional status of erythrocytes were evaluated at baseline, after 3 and 7 days of treatment. Results. The highest efficacy of antiaggregant therapy was observed in patients receiving antiplatelet combination. In this group there was a maximal reduction of erythrocyte aggregation and a number of pathological erythrocytes in peripheral blood by the 3rd day of therapy. This effect was increasing by the 7th day. Conclusion. The effect of all antiplatelet drugs was significant. The antiaggregant effect of clopidogrel was more significant than this for acetylsalicylic acid. Efficacy of combined therapy was higher than these for each drug alone.